2021
DOI: 10.48175/ijarsct-819
|View full text |Cite
|
Sign up to set email alerts
|

Certain Investigations on Military Applications of Wireless Sensor Networks

Abstract: Now a day’s Wireless Sensor Network (WSN) tends to attracts scientific community and its applications become the topic for many studies. This has been made possible by availability; especially in sensors have gotten smaller, cheaper and smarter in recent years. In order to form a network, these sensors are equipped with wireless interfaces by which they can communicate with each other. The use of and the ability to organise these sensors into networks have revealed several research challenges and have highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The types of sensors and their capabilities determine and limit the use of WSN in defined scenarios, as presented in Table I. The performance of the military WSNs application depends on many factors, including sensor capabilities, type of sensors, the wireless communication architecture, its range and appropriate data processing [5], [6].…”
Section: Related Workmentioning
confidence: 99%
“…The types of sensors and their capabilities determine and limit the use of WSN in defined scenarios, as presented in Table I. The performance of the military WSNs application depends on many factors, including sensor capabilities, type of sensors, the wireless communication architecture, its range and appropriate data processing [5], [6].…”
Section: Related Workmentioning
confidence: 99%
“…Through combing, it is found that relevant studies on "supply-side reform" in the sports industry have been elaborated, and it is generally believed that the sports industry in China A has ushered in a golden period of development, and the supply-side reform should be used to improve the scale and optimize the structure of the industry, to facilitate the optimal allocation of the factors and resources of the sports industry and let more public enjoy the fruits of development. However, most of the studies are based on the discussion and research of the whole sports industry [5], and there are fewer descriptions of the supply-side reform of mass sports events. The literature studied the theoretical framework and operation model of sports event operation, analyzed the current situation of sports event operation in country A concerning advanced sports event operation and management concepts, and proposed to build a sports event operation and management model with characteristics for optimization of sports event management system.…”
Section: Journal Of Sensorsmentioning
confidence: 99%
“…Wireless sensor network is a highly interdisciplinary research field, which has a very broad research prospect and can be widely used in battlefield reconnaissance, agricultural industrial measurement and control, electronic medical health and smart home, etc. [2,3]. However, with the diversification of network attacks and the complexity of node deployment environments, it is of great theoretical and practical importance to study an intrusion detection method with low energy consumption and efficient detection of multiple attacks [4,5].…”
Section: Introductionmentioning
confidence: 99%